2013
DOI: 10.3189/2013jog12j197
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a GRACE global mascon solution for Gulf of Alaska glaciers

Abstract: ABSTRACT. We present a high-resolution Gravity Recovery and Climate Experiment (GRACE) mascon solution for Gulf of Alaska (GOA) glaciers and compare this with in situ glaciological, climate and other remote-sensing observations. Our GRACE solution yields a GOA glacier mass balance of -65 AE 11 Gt a GRACE data compared well with in situ measurements at Wolverine Glacier (maritime Alaska), but poorly with those at Gulkana Glacier (interior Alaska). We conclude that, although GOA mass estimates from GRACE are rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 54 publications
6
59
0
Order By: Relevance
“…This can be related to ice mass loss once glacial isostatic adjustment has been accounted for Velicogna and Wahr 2006;Chen et al 2006b;Wouters et al 2008;Velicogna 2009;Velicogna and Wahr 2013). Examples of other regions of the cryosphere concerned with documented linear trends include Alaskan mountain glacier melting (Chen et al 2006a;Arendt et al 2013;Larsen et al 2015) and icefield melting in Patagonia (Chen et al 2007b;Ivins et al 2011). Strong linear trends located close to the Hudson Bay have been related to glacial isostatic adjustment (Tamisiea et al 2007), and recent studies focusing on Arctic regions showed that both isostatic and hydrological trends contribute to the observed signals (Frappart et al 2011a;Wang et al 2013).…”
Section: Linear Trendsmentioning
confidence: 99%
“…This can be related to ice mass loss once glacial isostatic adjustment has been accounted for Velicogna and Wahr 2006;Chen et al 2006b;Wouters et al 2008;Velicogna 2009;Velicogna and Wahr 2013). Examples of other regions of the cryosphere concerned with documented linear trends include Alaskan mountain glacier melting (Chen et al 2006a;Arendt et al 2013;Larsen et al 2015) and icefield melting in Patagonia (Chen et al 2007b;Ivins et al 2011). Strong linear trends located close to the Hudson Bay have been related to glacial isostatic adjustment (Tamisiea et al 2007), and recent studies focusing on Arctic regions showed that both isostatic and hydrological trends contribute to the observed signals (Frappart et al 2011a;Wang et al 2013).…”
Section: Linear Trendsmentioning
confidence: 99%
“…During the period 2003-09 their rate of mass loss was ∼50 Gt a À1 , ∼1/5 of the mass loss of the global glaciers excluding ice sheets (Gardner and others, 2013). The largest mass losses are found in the maritime climates around the Gulf of Alaska (Arendt andothers, 2002, 2013;Berthier and others, 2010). The mass loss of Alaska's glaciers is expected to continue; for example, Radićand others (2013) project losses between 18 and 45% by the end of the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating mass loss (e.g., Larsen et al, 2007;Berthier et al, 2010;Arendt et al, 2013;Larsen et al, 2015) and glacier dynamics (e.g., O'Neel et al, 2001O'Neel et al, , 2003 at Alaskan glaciers cover the Stikine Icefield, which is a small fraction of these generally regional studies. These studies lack the resolution to discern individual glaciers (e.g., Arendt et al, 2013), have incomplete coverage (e.g., Larsen et al, 2015), or do not incorporate the most recent data (e.g., Larsen et al, 2007;Berthier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These studies lack the resolution to discern individual glaciers (e.g., Arendt et al, 2013), have incomplete coverage (e.g., Larsen et al, 2015), or do not incorporate the most recent data (e.g., Larsen et al, 2007;Berthier et al, 2010). We update mass loss estimates for the Stikine Icefield by calculating thinning rates ( models (DEMs) derived from satellite stereo-optical data and compare these results with airborne LIDAR centerline elevation tracks.…”
Section: Introductionmentioning
confidence: 99%